Integrating The ASSURE Model in Animation Based Differentiated Instruction for Arabic Language Learning - Yasmadi Yasmadi; Sri Indah Lestari; Ilya Husna; David D Perrodin (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
An appropriate and student-centered learning strategy is highly needed, especially to accommodate the diverse abilities, interests, and learning styles of students. This study aims to explore the use of the ASSURE model in differentiated Arabic language learning using the Plotagon application. The study was conducted on 30 seventh-grade students at MTs Qur’anic Scientia in the 2025/2026 academic year. This study employs a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. This study employs the six stages of the ASSURE model to analyze research findings. The findings indicate that the use of differentiated learning, facilitated by Plotagon media, can address the diverse characteristics of students and enhance their engagement and desire to learn. When communicating in Arabic, students demonstrate high enthusiasm, active participation, and increased self-confidence. These results reinforce the belief that the use of learning media that aligns with students' characteristics enhances the learning process. This study confirms that the ASSURE model and digital animation media can function as an innovative alternative to improve the quality of Arabic language learning in madrasahs.